A note on learning in a credit economy - Pei Kuang (University of Birmingham, Birmingham Business School, 2014)
This paper studies the interaction of agents' collateral price beliefs, credit constraint and aggregate economic activity over the business cycle. Learning strengthens the role of collateral constraints in aggregate fluctuations. Under heterogeneous learning rules, numerical simulations illustrate that bankruptcy on the part of borrowers arises sooner as they track the economy faster.
Keywords: D83; E44; G14; 330; Learning; Collateral Constraint; Bankruptcy; Heterogeneity